Investigating Intention-To-Use Sharia Financial Technology In New Normal Era - Puspita, Rosana Eri; Senja, Puput Yanita; Pertiwi, Imanda Firmantyas Putri (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2020)
The new normal era has made digital-based industries with good prospects, including the sharia fintech industry. The aims of this study investigated the influence of knowledge about products, attitudes, and intentions-to-use of Sharia Financial Technology. There are three variables discussed in this study is knowledge about products, attitudes, and intentions. The quantitative approach used with this research using a regression test. Data Collected by an online survey of 60 respondents. The results of this study indicate that knowledge of Sharia Fintech affects attitudes and the intention-to-use Sharia Fintech. This study is limited to only Muslim respondents. Knowledge Products provide significant influence to shape attitudes and intentions. There has not been much research on new normal, including the sharia fintech industry. For practitioners, this research is useful as a reference in mapping the Muslim market in the fintech industry. This study highlights the importance of fintech in the new normal era because it can reduce the spread of the covid-19 virus.